Teknik Token Ekonomi untuk Meningkatkan Kedisiplinan Siswa di SD Muhammadiyah Gresik - Amin Mufidah; Muhimmatul Hasanah (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
This research discusses the Economic Token Technique Method for Improving Student Discipline at Muhammadiyah Gresik Elementary School. The aim of this research is to determine the effectiveness of the economic token intervention model to help students be more disciplined during the teaching and learning process for grade 2 students at Muhammadiyah Elementary School. The method used in this research is a quantitative method. The problem in this research is that students have low disciplinary attitudes when in class and also during the teaching and learning process. This is because the subject is a person who is not comfortable studying and remaining silent in class for a long time. In this problem, to overcome this problem, behavior modification is carried out using the token economy technique. The subject used in this research was 1 boy from class 2 of SD Muhammadiyah Gresik who had a low disciplinary attitude. This research aims to determine the increase in student discipline by modifying behavior using the token economy technique. In the implementation, research subjects were given intervention or treatment in the form of rewards by sticking stickers for 21 days with pretest, intervention and posttest stages, then their disciplinary attitudes were observed and at the end of the session if the target behavior that was changed showed good changes then the subject would be given a reward according to the agreement at the beginning. where the prize is exchanged for the number of stickers obtained during the session. This can be seen from the pretest results, the significance value obtained was 10 and for the posttest results the significance value obtained was 13. Based on the gain score calculation, it showed that the subject experienced an increase of 3 scores from the pretest score of 10 to 13. During the posttest this showed an increase but it was not significant.